PERTANGGUNGGUGATAN CV. ADI KURNIA DALAM KONTRAK KERJA KONTRUKSI AKIBAT WANPRESTASI - Nadia Elga Firmania (Dinamika, 2020)
ABSTRACTThe background of this thesis is the rapid development of infrastructure to support prosperous community life in the past five years. Therefore many governments use construction services to carry out infrastructure development work programs in Indonesia. Thesis problem formulation as follows: How are the Construction Contracts made by CV. Adi Kurnia with the Department of Public Housing and Settlement Area according to Positive Law? How is the form of accountability CV. Adi Kurnia due to defaults on the construction of the access road of Ngudal Feces Sludge Treatment Plant (IPLT), Ngawi District, Ngawi Regency? This empirical juridical research uses a sociological approach. The results of this study indicate the meaning of liability is accountability, namely responsibility arising from failure to meet standards, while the responsibility is realized in the form of compensation. Any party who violates a contract of work is called a default and the party who carries out the contract must be held accountable for any errors or omissions. Keywords : Liability, Construction Work Contracts, DefaultsABSTRAKLatar belakang skripsi ini adalah pesatnya pembangunan infrastruktur guna menunjang kehidupan masyarakat yang sejahtera di dalam lima tahun terakhir ini. Karenanya pemerintah banyak menggunakan jasa kontruksi untuk melaksanakan program kerja pembangunan infrastruktur di Indonesia. Rumusan masalah skripsi sebagai berikut: Bagaimana pengaturan Kontrak Kerja Kontruksi yang dibuat oleh CV. Adi Kurnia dengan Dinas Perumahan Rakyat dan Kawasan Pemukiman menurut Hukum Positif ? Bagaimana bentuk pertanggunggugatan CV. Adi Kurnia akibat wanprestasi terhadap pembangunan akses jalan Instalasi Pengolahan Lumpur Tinja (IPLT) Ngudal Kecamatan Ngawi Kabupaten Ngawi? Penelitian yuridis empiris ini dengan menggunakan pendekatan sosiologi. Hasil penelitian ini menunjukan Makna liability adalah tanggung gugat yakni tanggung jawab yang timbul dari kegagalan untuk memenuhi standar, sedangkan tanggungjawabnya diwujudkan dalam bentuk ganti rugi. Pihak yang melanggar kontrak kerja kontruksi  disebut wanprestasi dan pihak yang melakukan wanprestasi harus bertanggunggugat atas kesalahan ataupun kelalaiannya.Kata Kunci : Pertanggunggugatan, Kontrak Kerja Kontruksi, Wanprestasi